The other Emily - Koontz, Dean R. (Dean Ray), 1945- (Seattle : Thomas & Mercer, 2021)
Haunted by the unsolved disappearance of the love of his life a decade earlier, writer David Thorne visits her suspected killer in prison before meeting a woman who uncannily resembles the person he lost.
Keywords: Man-woman relationships -- Fiction; Cold cases (Criminal investigation) -- Fiction; Psychological fiction; Thrillers (Fiction)